The broader societal impacts of COVID-19 and the growing importance of capturing these in health economic analyses. (9th March 2021) - Schnitzler, Lena; Janssen, Luca M. M.; Evers, Silvia M. A. A.; Jackson, Louise J.; Paulus, Aggie T. G.; Roberts, Tracy E.; Pokhilenko, Irina
Abstract : Abstract The rapid spread of the current COVID-19 pandemic has affected societies worldwide, leading to excess mortality, long-lasting health consequences, strained healthcare systems, and additional strains and spillover effects on other sectors outside health (i.e., intersectoral costs and benefits). In this perspective piece, we demonstrate the broader societal impacts of COVID-19 on other sectors outside the health sector and the growing importance of capturing these in health economic analyses. These broader impacts include, for instance, the effects on the labor market and productivity, education, criminal justice, housing, consumption, and environment. The current pandemic highlights the importance of adopting a societal perspective to consider these broader impacts of public health issues and interventions and only omit these where it can be clearly justified as appropriate to do so. Furthermore, we explain how the COVID-19 pandemic exposed and exacerbated existing deep-rooted structural inequalities that contribute to the wider societal impacts of the pandemic.